Commensal Bacteria Increase Invasion of Intestinal Epithelium by Salmonella enterica Serovar Typhi - Lyczak, Jeffrey B. (American Society for Microbiology, 2003)
The intestinal microflora consists of a heterogeneous population of microorganisms and has many effects on the health status of its human host. Here, it is shown that the products of certain strains of bacteria normally present in the intestinal microflora are able to trigger redistribution of the cystic fibrosis transmembrane conductance regulator (CFTR) protein in epithelial cells. CFTR is used by Salmonella enterica serovar Typhi as a receptor on epithelial cells which mediate the translocation of this microorganism to the gastric submucosa. Serovar Typhi-epithelial cell adhesion and CFTR-dependent invasion by serovar Typhi of epithelial cells were increased following commensal-mediated CFTR redistribution. These data suggest that commensal microorganisms present in the intestinal lumen can affect the efficiency of serovar Typhi invasion of the intestinal submucosa. This could be a key factor influencing host susceptibility to typhoid fever.